The semantics of graduation in political speeches: a case of President Robert Mugabe's speeches officially opening the Zimbabwean parliament - Jakaza, Ernest; Visser, MW (UNISA Press, 2016)
The study of political speeches has been generally conducted from rhetoric, dialectic, conversational analysis, critical discourse analysis, dialogism and speech act theory. This article seeks to depart from such theoretic perspectives to the analysis of political speeches by presenting evidence that the linguistic discourse analytical framework of Appraisal Theory provides alternative ways of perceiving the nature of language use in the context of political speeches. Much attention in the utilisation of the Appraisal theory has been applied to the two sub-systems of attitude and engagement. The researchers' focus in this study is to depart from the two sub-systems and explore the semantics of graduation as realised in Mugabe's political speeches officially opening the Seventh Parliament of Zimbabwe. The impact that this graduation has on the message being communicated and the relations maintained, nurtured or built have important linguistic or discourse-linguistic insights.